2018
DOI: 10.1108/ilt-02-2017-0028
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of depositing uniform and wear-resistant diamond films on massive mechanical seals

Abstract: Purpose This study aims to obtain diamond-coated mechanical seals with improved sealing performance and considerable cost. To achieve this purpose, the study focuses on depositing uniform, wear-resistant and easily polished diamond coatings on massive mechanical seals in a large-scale vacuum chamber. Design/methodology/approach The computational fluid dynamics simulation test and its corresponding deposition experiment are carried out to improve the uniformity of diamond films on massive mechanical seals. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…As abrasive tools are fabricated by plenty of SCD grits, the mechanical wear of abrasive machining is extremely complex (He et al, 2018). Thus, single SCD grit scratching process is a significant and effective method to investigate the complex mechanical wear mechanism of abrasive precision machining and ultra-precision machining process Wang, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As abrasive tools are fabricated by plenty of SCD grits, the mechanical wear of abrasive machining is extremely complex (He et al, 2018). Thus, single SCD grit scratching process is a significant and effective method to investigate the complex mechanical wear mechanism of abrasive precision machining and ultra-precision machining process Wang, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a mechanical seal face designed in combination with a polycrystalline diamond (PCD) coating could offer an outstanding abrasion resistance and, at the same time, a considerably improved performance under poor lubrication conditions like in high-viscosity fluids and even in dry-running condition due to the low friction coefficient. Numerous studies have confirmed that the diamond coatings considerably lower the friction and enhance the tribological performance in mechanical face seals [2,[4][5][6][7][8][9][10][11][12][13][14]. However, there are few researches on the upper limit of mechanical seals with PCD coating application under conditions where the combination of high pressure and high surface speeds create high levels of pressure-velocity (PV).…”
Section: Introductionmentioning
confidence: 99%